2013
DOI: 10.1038/nphys2702
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic exchange, spin–orbit coupling and spiral magnetism at the LaAlO3/SrTiO3 interface

Abstract: The electronic properties of the polar interface between insulating oxides is a subject of great interest 1-3 . An exciting development is the observation of robust magnetism 4-8 at the interface of two non-magnetic materials, LaAlO 3 (LAO) and SrTiO 3 (STO). Here we present a microscopic theory for the formation and interaction of local moments that depends on essential features of the LAO/STO interface. We show that correlation-induced moments arise owing to interfacial splitting of orbital degeneracy. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
208
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(220 citation statements)
references
References 32 publications
(34 reference statements)
4
208
4
Order By: Relevance
“…The mechanism depends on the relative density of localized versus itinerant electrons, as well as their orbital character 20,31,32 . Fidkowski et al 32 describe a ferromagnetic Kondo model in which local d xy moments couple ferromagnetically to delocalized d xz /d yz carriers; models with ferromagnetic exchange are also described by Joshua et al 20 and Bannerjee et al 33 Michaeli et al 34 describe a model based on Zener (antiferromagnetic) exchange between localized and delocalized d xy carriers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism depends on the relative density of localized versus itinerant electrons, as well as their orbital character 20,31,32 . Fidkowski et al 32 describe a ferromagnetic Kondo model in which local d xy moments couple ferromagnetically to delocalized d xz /d yz carriers; models with ferromagnetic exchange are also described by Joshua et al 20 and Bannerjee et al 33 Michaeli et al 34 describe a model based on Zener (antiferromagnetic) exchange between localized and delocalized d xy carriers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…a spin polarization of the q2DES, but not necessarily to a magnetic order. This is an intriguing result, which requires further investigations, also in view of recent theoretical proposal of spiral magnetism in q2DES [82].…”
Section: Magnetism At the Laalo 3 /Srtio 3 Interfacementioning
confidence: 99%
“…Interestingly, the-7 oretical calculations have found that clusters of oxygen vacancies could induce an orbital reconstruction, generating an interfacial magnetic state with a dominant contribution from the d xy states to the magnetic moment and an exchange energy splitting as large as a fraction of eV [29,30]. Alternative models, based the interfacial splitting of t 2g orbital degeneracy in combination with electron correlations, have also been proposed [2,[31][32][33][34].It is interesting to contrast our findings with the case of spin-polarized quantum well states in ultra-thin films of non-magnetic materials grown on ferromagnetic surfaces, like e.g. Cu/Co(001) [35,36].…”
mentioning
confidence: 99%